2007
DOI: 10.11646/zootaxa.1440.1.1
|View full text |Cite
|
Sign up to set email alerts
|

A review of the genus Pareuchiloglanis (Sisoridae) from the Lancangjiang (upper Mekong River) with descriptions of two new species from Yunnan, China

Abstract: This study reports five species of Pareuchiloglanis in the Lancangjiang drainage of China, including descriptions of two new species: P. abbreviatus sp. nov., P. gracilicaudata, P. kamengensis, P. myzostoma and P. prolixdorsalis sp. nov. The two new species are distinguished from P. feae, P. poilanei, P. sichuanensis and P. tianquanensis by a shorter adipose-fin base and the adipose-fin base being separated from the caudal fin, differ from P. sinensis, P. macrotrema, P. longicauda and P. rhabdurus by a more re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
21
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 6 publications
0
21
0
Order By: Relevance
“…Chu (1981) resurrected the genus Pareuchiloglanis Pellegrin, 1936, for species in the genus Euchiloglanis by inspecting the form of premaxillary tooth bands of the type species, E. davide. Both morphological and molecular phylogenetic analyses for the glyptosternoid fishes did not support the monophyly of Pareuchiloglanis (He 1995;Peng et al 2004;Guo et al 2005), and the twenty species can be divided into two groups according to external morphology (Li et al 2007). Recently, Zhou et al (2011) erected a new genus Creteuchiloglanis based on three species previously assigned to Pareuchiloglanis, and described two new species in this genus.…”
Section: Discussionmentioning
confidence: 99%
“…Chu (1981) resurrected the genus Pareuchiloglanis Pellegrin, 1936, for species in the genus Euchiloglanis by inspecting the form of premaxillary tooth bands of the type species, E. davide. Both morphological and molecular phylogenetic analyses for the glyptosternoid fishes did not support the monophyly of Pareuchiloglanis (He 1995;Peng et al 2004;Guo et al 2005), and the twenty species can be divided into two groups according to external morphology (Li et al 2007). Recently, Zhou et al (2011) erected a new genus Creteuchiloglanis based on three species previously assigned to Pareuchiloglanis, and described two new species in this genus.…”
Section: Discussionmentioning
confidence: 99%
“…Comparisons of type specimens of P. feae with specimens from Yunnan that were used in the studies of He (1995, 1996) and Li et al (2007) showed that P. feae is known only from Myanmar and is more closely related to species of Pareuchiloglanis than to the specimens from Yunnan. All records of P. feae from Yunnan are either misidentifications of P. macropterus or are based on an unnamed species related to P. gongshanensis, P. kamengensis, and P. macropterus.We propose a new genus for the three species of the second group of Li et al (2007), along with the unnamed species represented by the Yunnan populations previously identified as P. feae, and another previously identified as P. kamengensis from the Lancang-Jiang drainage (upper Mekong River), China. Those two new species are named herein, and diagnoses are provided for the other species of Creteuchiloglanis.…”
mentioning
confidence: 97%
“…We propose a new genus for the three species of the second group of Li et al (2007), along with the unnamed species represented by the Yunnan populations previously identified as P. feae, and another previously identified as P. kamengensis from the Lancang-Jiang drainage (upper Mekong River), China. Those two new species are named herein, and diagnoses are provided for the other species of Creteuchiloglanis.…”
mentioning
confidence: 99%
See 2 more Smart Citations